2020
DOI: 10.1007/s00106-019-00767-2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based diagnostic use of VEMPs

Abstract: Evidence-based diagnostic use of VEMPs From neurophysiological principles to clinical application Electronic supplementary material The online version of this article (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 84 publications
(167 reference statements)
0
13
0
4
Order By: Relevance
“…Other NMSs disorders were also associated with VEMP responses, including sleep, perception, cognition, urinary problems, cardiovascular, and sexual dysfunction, although seemingly unrelated to vestibular function 6 , 9 , 10 . It was explained by the degeneration of several brainstem nuclei responsible for the motor and NMSs 9 , and by the VEMP circuit that spans the midbrain, the pons, and the medulla 14 , 15 . Considering our results that patient dizziness may result from vestibular dysfunction and the fact that VEMPs are useful to evaluate the vestibular system, we think that it may be clinically reasonable that VEMPs reflect dizziness rather than other NMSs in PD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other NMSs disorders were also associated with VEMP responses, including sleep, perception, cognition, urinary problems, cardiovascular, and sexual dysfunction, although seemingly unrelated to vestibular function 6 , 9 , 10 . It was explained by the degeneration of several brainstem nuclei responsible for the motor and NMSs 9 , and by the VEMP circuit that spans the midbrain, the pons, and the medulla 14 , 15 . Considering our results that patient dizziness may result from vestibular dysfunction and the fact that VEMPs are useful to evaluate the vestibular system, we think that it may be clinically reasonable that VEMPs reflect dizziness rather than other NMSs in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The oVEMP pathway presumably starts from the vestibular nucleus, crosses the midline, and ascends through the medial longitudinal fasciculus (MLF) at the upper pons and midbrain level, then to the ocular motor nuclei. The cVEMP presumably involves a descending pathway from the vestibular nucleus, ipsilateral medial vestibulospinal tract in the pons and medulla, then to the accessory motor neurons 14 , 15 . It has been suggested that upper brainstem function might be involved and lower brainstem function preserved in early PD patients 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Even if the acoustic sensitivity of the macula organs is only rudimentary in humans and evolution has provided for a largely independent functioning of the auditory and vestibular organs despite the anatomical connection 3 , it can still be used for diagnostic purposes: Stimulation of the otolith organs by sound, vibration, or galvanic stimuli may trigger a vestibular reflex that can be objectified by recording vestibular evoked myogenic potentials (VEMPs) 4 . In the case of suprathreshold stimulation with e. g. 500 Hz stimuli via air or bone conduction, potentials corresponding to the neuronal projections of saccule and utricle can be measured by means of electrodes at the contralateral eye muscles (oVEMPs, utricle) or the ipsilateral sternocleidomastoid muscle (cVEMPs, saccule) and the function of the macula organs can be assessed.…”
Section: Anatomy and Physiologymentioning
confidence: 99%
“…To test the function of the saccule and the utricle, cervical vestibular evoked myogenic potentials (cVEMPs) and ocular vestibular myogenic potentials (oVEMPs) were used, respectively, as described before (28,29). cVEMP testing was conducted according to international guidelines using the Eclipse hardware (Interacoustics A/S, Middelfart, Denmark) while the test subject was sitting in a chair.…”
Section: Vestibular Testingmentioning
confidence: 99%
“…For every cVEMP and oVEMP recording, two runs were performed to demonstrate reproducibility, and responses were averaged. Asymmetry ratios (ARs) for oVEMP and cVEMP amplitudes were calculated as described previously, and an AR > 0.4 was considered to indicate a significant difference between the responses of both ears (28).…”
Section: Vestibular Testingmentioning
confidence: 99%